Organic solar cells with very high fill factor and voltage using tetrapropyl-tetraphenyl-diindenoperylene as green donor - Meiss, J; Hummert, M; Ziehlke, H; Leo, K; Riede, M (Wiley, 2010)
We present 2,3,10,11-tetrapropyl-1,4,9,12-tetraphenyl-diindeno[1,2,3-cd:1′,2′,3′-lm]perylene (P4-Ph4-DIP) as new green donor for small molecule organic solar cells (SMOSC). P4-Ph4-DIP absorbs in the green spectral range of 490-580 nm and thus is a decisive building block towards broad coverage of the sun spectrum. SMOSC with P4-Ph4-DIP as donor and C60 as blue-absorbing acceptor display very high fill factors FF > 76% and open circuit voltages of 0.99 V, reaching η = 1.92% for 12 nm P4-Ph4-DIP. Current voltage and external quantum efficiency spectra suggest that an exciton diffusion length ED < 20 nm is the main limiting factor. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.